The Seed–Seedling Transition in Commercial Soybean Cultivars with the Presence of Greenish Seeds in the Sample: A Perspective from Classical Genetic Parameters - Ajala-Luccas, Daiani; Ribeiro-Oliveira, João Paulo; Teixeira, Renake N.; Ducatti, Karina Renostro; França-Neto, J. B.; Hilhorst, Henk W. M.; da Silva, Edvaldo Aparecido Amaral [UNESP] (MDPI, 2023)
Chlorophyll retention reduces the quality of soybean grain and seeds, but little is known about the relationship between this anomaly and the seed–seedling transition or classical genetic breeding. Taking this into account, we provide a new perspective about how greenish seeds are associated with genetic material. For that, we used seed–seedling transition measurements of nine commercial cultivars cultivated by different seed farmers. Our findings demonstrated that: (i) The anomaly of greening in soybean seeds seems to be more expressed as a function of thermal variation than rainfall; (ii) There are commercial cultivars with distinct sensitivity to the greening phenotype, indicating potential for classical breeding for the species; (iii) The seed–seedling transition is significantly modified by the presence of greenish seeds, and the diagnosis of their presence can be anticipated by the analysis of embryo protrusion.
Keywords: commodity; global changes; Glycine max; heritability; physiological anomaly; seed technology and physiology